The 1848 revolutions and European political thought - Moggach, Douglas; Stedman Jones, Gareth 1942- (Cambridge University Press, 2018)
The revolutions that swept across Europe in 1848 marked a turning-point in the history of political and social thought. They raised questions of democracy, nationhood, freedom and social cohesion that have remained among the key issues of modern politics, and still help to define the major ideological currents - liberalism, socialism, republicanism, anarchism, conservatism - in which these questions continue to be debated today. This collection of essays by internationally prominent historians of political thought examines the 1848 Revolutions in a pan-European perspective, and offers research on questions of state power, nationality, religion, the economy, poverty, labour, and freedom. Even where the revolutionary movements failed to achieve their explicit objectives of transforming the state and social relations, they set the agenda for subsequent regimes, and contributed to the shaping of modern European thought and institutions
Keywords: Revolutions / Europe / History / 19th century; Political science / Europe / History / 19th century; Revolution -- 1848; Europagedanke; Europe / History / 1848-1849; Aufsatzsammlung